4(2x+1)+7=7(4x-3)

Simple and best practice solution for 4(2x+1)+7=7(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+1)+7=7(4x-3) equation:


Simplifying
4(2x + 1) + 7 = 7(4x + -3)

Reorder the terms:
4(1 + 2x) + 7 = 7(4x + -3)
(1 * 4 + 2x * 4) + 7 = 7(4x + -3)
(4 + 8x) + 7 = 7(4x + -3)

Reorder the terms:
4 + 7 + 8x = 7(4x + -3)

Combine like terms: 4 + 7 = 11
11 + 8x = 7(4x + -3)

Reorder the terms:
11 + 8x = 7(-3 + 4x)
11 + 8x = (-3 * 7 + 4x * 7)
11 + 8x = (-21 + 28x)

Solving
11 + 8x = -21 + 28x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28x' to each side of the equation.
11 + 8x + -28x = -21 + 28x + -28x

Combine like terms: 8x + -28x = -20x
11 + -20x = -21 + 28x + -28x

Combine like terms: 28x + -28x = 0
11 + -20x = -21 + 0
11 + -20x = -21

Add '-11' to each side of the equation.
11 + -11 + -20x = -21 + -11

Combine like terms: 11 + -11 = 0
0 + -20x = -21 + -11
-20x = -21 + -11

Combine like terms: -21 + -11 = -32
-20x = -32

Divide each side by '-20'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| 5(q+2)+2q=1 | | -2x=-70 | | -3(x+9)=12 | | 23x-7=5 | | -4-3x=10x-6 | | 8h=16-6h | | 2d+4(3d+2)= | | 5a+3(a+4)= | | 9n-17=6n+7 | | 5(3x+4)=50 | | 2x+x+3x=6 | | -12,720+20x=0 | | 4x+(x+7)=-28-2x | | 5(x.2)=40/2 | | 1.6n=0.8n | | y=10x+4 | | 3x^4-30x^2-33=0 | | 4+2n=8n+16 | | -8+s=-56 | | 2x+y=-11 | | 7x=10x-5 | | 3.3=0.15x | | 6x+13=-17 | | 5(3p+2)-3(5p-3)= | | x+3x-5x-15= | | c+14=-13 | | 7y=6y-1 | | 7(r-4)-(-4+4r)=-r+4+2r | | (5x-7)(2x+1)-10x(x-4)=0 | | 3y=2y-5 | | f+f+f= | | 6v+18=35t |

Equations solver categories